A complete unknown [videorecording (Blu-Ray)] - Mangold, James; Cocks, Jay; Chalamet, Timothée; Norton, Edward; Fanning, Elle, 1998-; Barbaro, Monica, 1989-; Holbrook, Boyd, 1981-; Fogler, Dan; Butz, Norbert Leo; Hatsune, Eriko, 1982-; Morganfield, Big Bill, 1956-; Harrison, Will, 1996-; et al. (Searchlight Pictures, 2025)
New York, 1961. Against the backdrop of a vibrant music scene and tumultuous cultural upheaval, an enigmatic 19-year-old from Minnesota named Bob Dylan arrives with his guitar and revolutionary talent, destined to change the course of American music. He forges intimate relationships with music icons of Greenwich Village on his meteoric rise, culminating in a groundbreaking and controversial performance that reverberates worldwide.